Astragaloside IV Alleviates Tacrolimus-Induced Chronic Nephrotoxicity via p62-Keap1-Nrf2 Pathway - Gao, Ping; Du, Xiaoyi; Liu, Lili; Xu, Hua; Liu, Maochang; Guan, Xinlei; Zhang, Chengliang (Frontiers in Pharmacology, 2021)
Tacrolimus-induced chronic nephrotoxicity (TIN) hinders its long-term use in patients. However, there are no drugs available in the clinic to relieve it at present. Astragaloside IV (AS-IV) is a saponin extract of the Astragalus which is widely used in the treatment of kidney disease. This study aimed to investigate the effect of AS-IV on TIN and its underlying mechanism. Herein, C57BL/6 mice were treated with tacrolimus and/or AS-IV for 4 weeks, and then the renal function, fibrosis, oxidative stress and p62-Keap1-Nrf2 pathway were evaluated to ascertain the contribution of AS-IV and p62-Keap1-Nrf2 pathway to TIN. Our results demonstrated that AS-IV significantly improved renal function and alleviated tubulointerstitial fibrosis compared with the model group. The expression of fibrosis-related proteins, including TGF-β1, Collagen I and α-SMA, were also decreased by AS-IV. Furthermore, AS-IV relieved the inhibition of tacrolimus on antioxidant enzymes. The data in HK-2 cells also proved that AS-IV reduced tacrolimus-induced cell death and oxidative stress. Mechanistically, AS-IV markedly promoted the nuclear translocation of Nrf2 and the renal protective effects of AS-IV were abolished by Nrf2 inhibitor. Further researches showed that phosphorylated p62 was significantly increased after AS-IV pretreatment. Moreover, AS-IV failed to increase nuclear translocation of Nrf2 and subsequent anti-oxidative stress in HK-2 cells transfected with p62 siRNA. Collectively, these findings indicate that AS-IV relieve TIN by enhancing p62 phosphorylation, thereby increasing Nrf2 nuclear translocation, and then alleviating ROS accumulation and renal fibrosis.